The state of legal education in Malaysia - Nik Mahmod, Nik Ahmad Kamal (2010)
A bachelor degree in law is still considered a prestigious professional qualification that enables the holder to enter into the legal profession. Over the years many public and private universities are offering the programmes. Questions are raised about the quality of legal personnel and legal practitioners produced by local and overseas institutions. The paper seeks to evaluate the teaching and learning process and methods in law schools as well as other trainings programmes that are intended to provide a holistic inputs to law students. It also presents a perception survey conducted on the quality of lawyers and legal personnel produced by local and overseas institutions.